A business framework to survive the COVID-19 pandemic: A multiple case study on the dynamic capabilities and improvisational capabilities among selected food service MSMEs - Portugal, Enrico Miguel Y. (Animo Repository, 2022)
Purpose: This paper explored the concept of dynamic capabilities and improvisational capabilities in the pandemic in the food services industry in the Philippines. Furthermore, this study focused on the theories of dynamic capabilities, improvisational capabilities, and turbulent environments. Design/methodology/approach: The researchers conducted interviews with two MSMEs in the food service industry to understand how they adapted to the pandemic. The researchers synthesized the data using thematic analysis and created a general model or framework that other companies can use with the information gathered. Research limitations/implications: This research’s main implication was that it took place during the height of the pandemic, ergo not many similar studies were published on the matter. Furthermore, the researchers used a more flexible criteria to acquire enough respondents to pursue the study. However, the researchers preferred to garner more interviewees for deeper analysis. Another limitation was that while the researchers interviewed similar ranking employees but of different experience and perspectives, hence the differences in answers and understanding for some questions. Lastly, this research was limited to only the food services industry, as the researchers wanted to focus on one primary industry to get a better grasp of the conditions it faces. Opportunities for future research include focusing on different industries or focusing the research on another kind of business (e.g., social enterprises, NGOs). Practical and social implications: This research explained how businesses recovered through combining both dynamic and improvisational capabilities and not solely depending on only one or the other. Key Words: dynamic capabilities, improvisational capabilities, COVID-19, management, turbulent environment, food service industry